VARIOUS THEORIES ON THE ORIGIN OF THE UD INSTRUMENT - Hasanov Azamat Oktamovich (Western European Studies, 2025)
This article analyzes various theories concerning the origin of the ud, one of the most significant instruments of the Near Eastern musical culture. Based on similarities with ancient instruments and the presence of ud-like instruments in the civilizations of Ancient Egypt, Mesopotamia, Persia, and the Arab world, the discussion explores which of them may be considered the direct ancestor of the ud. The ideas proposed in archaeological, historical, and iconographic sources are evaluated according to scientific criteria
Keywords: Instrument; Sound; Theory; Eastern music